Karakteristik Pertumbuhan Akar dan Tajuk dua Varietas Lada Perdu (Piper nigrum L.) dengan Perlakuan Cekaman Naungan - Nasution, Siti Aminah; Hanum, Chairani; Ginting, Jonatan (Jurnal Online Pertanian Tropik, 2018)
Morphological observations were a preliminary identification for plant adaptation to shading stress. This research was conducted at Cengkeh Turi, North Binjai Subdistrict (32 meters above sea) from April to June 2017, used Split Plot Design. The main plot was shade (0, 25, 50 and 75%) and the sub plot was pepper varieties (Bengkayang and Lokal Binjai). The results showed that two varieties of pepper used have the same responses on the shoot dry weight, root dry weight, number of leaf area. Shading stress treatment had a significant effect on shoot dry weight and the number of leaf areas. Lokal Binjai was more adaptive to shading stress compared to Bengkayang. Light intensity 25% it is a good condition for two varieties of pepper